Design of Quantum Learning-Based Numeracy Worksheet on Uncertainty and Data Content - Fathimatuz Zahro Maulidiyah; Siti Nuriyatin; Nurina Ayuningtyas (Jurnal VARIDIKA, 2024)
Previous study attempted to create worksheets to boost students' comprehension and numeracy skills. However, there is little research on designing numeracy worksheets using Quantum Learning. This study intends to provide uncertainty-and-data-content-of-numeracy worksheets using Quantum Learning to help students enhance their grasp of probability material and numeracy skills. The incorporation of Numeracy into the uncertainty and data content worksheet distinguishes this study from past research. This is supported by earlier research, which suggests that incorporating Numeracy in worksheets can help pupils improve their numeracy skills. Furthermore, Numeracy, which is concerned with problem solving in a variety of real-world scenarios, adheres to Quantum Learning, whose learning stages connect the content to real life. This study employs the 4D development paradigm, which has been condensed into 3D: define, design, and develop. Data gathering methods include questionnaires, observation of learning implementation, and testing. The analysis is both descriptively qualitative and descriptively quantitative. This study involved 31 kids from one of Indonesia's junior high schools. The findings of this study show that the worksheet is valid, practical, and successful, indicating that it was doable. The study found that students' grasp of probability material improved, as did their numeracy skills. The worksheet creation will assist instructors to construct excellent mathematics learning combined with numeracy.